Pengaruh Metode Teams Games Tournament (Tgt) terhadap Minat Belajar Bahasa Indonesia Siswa Kelas IV di Mi Al Falah Beran - Elvina Nur Azizah; Dita Primashanti Koesmadi; Uci Ulfa Nur’afifah (LP. Ma'arif Janggan Magetan, 2024)
The aim of this study is to determine the impact of the Teams Games Tournament (TGT) method on the learning interest in Indonesian language among fourth-grade students at MI Al Falah ‘Beran, Ngawi. The study utilizes a quantitative research methodology and employs a One Group Pretest Posttest Design. The subjects related to the research object form the population. The population in this study comprises all students of MI Al Falah Beran Ngawi, totaling 600 students. The sample in this study consists of 27 fourth-grade students at MI Al Falah Beran. A questionnaire was used to collect data. In this study, the results of data analysis and the paired sample t-test demonstrate a significant impact of the TGT method on the interest in learning Indonesian among fourth-grade students at MI Al Falah Beran. Before the intervention, the students' learning interest was low; however, after the application of the TGT method, there was a significant change in the students' learning interest. This indicates that the TGT model has a positive impact on the students' desire to learn Indonesian language in fourth grade at MI Al Falah Beran.